Upaya Kepala Sekolah Dalam Meningkatkan Kinerja Guru Pendidikan Agama Islam Di Madarash Ibtidaiyah - Safran, Safran (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to explore the efforts made by the principal in improving the performance of Islamic Religious Education (PAI) teachers at Madrasah Ibtidaiyah Ali Imran Medan. Using a qualitative approach and case study design, the research collects data through observations, interviews with the principal, PAI teachers, and administrative staff, as well as document analysis. The findings reveal that the principal implements transformational leadership to inspire and motivate teachers, and participative leadership to involve teachers in decision-making processes. The principal also emphasizes professional development through relevant training programs. However, challenges such as limited resources, resistance to change, and lack of support from parents remain significant barriers to improving teacher performance. Despite these obstacles, the principal continues to create a supportive environment for teacher development. This study contributes to understanding the role of school leadership in improving teacher performance, offering practical insights for school management and policy development.